Effect of deastringency treatment of intact persimmon fruits on the quality of fresh-cut persimmons. (1st January 2015) - Chung, Hun-Sik; Kim, Han-Soo; Lee, Young-Guen; Seong, Jong-Hwan
Highlights: Warm-water deastringency pretreatment inhibited browning of fresh-cut persimmons. Warm-water deastringency pretreatment retarded softening of fresh-cut persimmons. Deastringency treatment reduced antioxidant activity of fresh-cut persimmons. Abstract: The changes in the quality characteristics of the fresh-cut products prepared from intact 'Cheongdobansi' persimmons treated with different deastringency methods (nontreated, carbon dioxide gas, warm water, ethanol vapour) have been investigated for 6 days at 10 °C. Flesh firmness of the persimmons decreased after ethanol vapour treatment. The decrease in L ∗ value and flesh firmness in the slices prepared from persimmons treated with warm water was retarded. Soluble solids content and titratable acidity of the persimmons decreased after all deastringency treatments. Soluble tannins and radical scavenging activity of the slices from untreated persimmons were maintained at higher concentrations, unlike slices from astringency-removed persimmons. These results suggest that pre-slicing deastringency treatments affect the characteristics of fresh-cut persimmons, and that warm-water treatment could be a useful method to control the browning and softening of fresh-cut persimmons.